Psychological indicators of overtraining in high level judo athletes in pre- and post-competition periods - Noce, F.; Teoldo Costa, V.; Szmuchrowski, L. A.; Serra Soares, D.; de Mello, M. T. (Archives of Budo, 2014)
Background and Study Aim: Given the psychological, physiological and nutritional demands of elite sport judo, it is not surprising that many athletes struggle to optimize training. Overtraining is the result of an imbalance between stress and recovery, as result of short recovery time and psychosocial events. The aim of this study is knowledge about the psychological indicators of overtraining in elite judo athletes during pre- and post-competition periods. Material and Methods: Forty-eight judo athletes from an elite team took part in this study. They were grouped by age, 24 junior (up to 18 years) and 24 senior (over 18 years). For the assessment of psychological indicators of overtraining the stress and recovery questionnaire RESTQ-Sport questionnaire in the last practice before competition and in the first practice after competition. It comprises 76 items organized in 19 general scales. Results: Only two scales presented significant differences between the pre- and post-competition periods for the entire group (n = 48): the "fatigue" scale of the general stress dimension and "success" in the general recovery dimension. The comparison of the age groups in the pre-competition period resulted in significant differences in 9 out of the 19 scales and in the four dimensions. The male athletes` profile was more positive than the junior athletes` profile. In the post-competition period, significant differences were observed in 3 out of the 19 scales. A similar result pattern was observed; the senior athletes had a more positive profile. The longer sports practice time, and consequently more competition experience at this level, may have contributed to the differences between the age groups. Such a fact may be observed in the perception of pre- and post-competition performance. The junior athletes felt less prepared in the evaluated aspects than the senior athletes, especially in "technique" (p = 0.002). The low performance values in competition indicate that the group did not achieve the expected result. Conclusions: Pre- and post-competition psychological indicators of overtraining may behave differently as a function of judo athletes` age. Older athletes tend to have a more positive profile than younger ones. The comparison between the psychological variables shows a greater difference in scores for age. The expectations in relation to the competition affected young athletes significantly.